MAQASID-DRIVEN HALAL ASSURANCE AND DIGITAL CO-CREATION IN SOCIAL COMMERCE: THE MAHACC MODEL FOR INDONESIA - Erwan Iskandar; Eman Sulaiman; Adi Santoso; Vigory Gloriman Manalu (PATEMON: Multidisciplinary Research, 2025)
Purpose: This conceptual paper develops an integrative model to explain how Indonesian consumers form preference and purchase intention toward halal cosmetics in social commerce, where information asymmetry and user-generated claims are pervasive. Research methodology: We conduct a theoretical review and theory-building synthesis across halal assurance and integrity, signaling theory, stimulus–organism–response (S‑O‑R), online trust and risk, value co-creation in social commerce, and platform governance. We integrate these streams with maqasid al-shariah to derive a new mechanism-based model. Results: We propose the MaHACC model (Maqasid-driven Halal Assurance and Co-Creation). A bundle of halal assurance signals, platform shariah governance, and co-creation affordances shapes Maqasid Congruence Appraisal and Amanah-based Digital Trust, which together predict preference, purchase intention, advocacy, and loyalty while reducing perceived halal risk. Limitations: This is a conceptual paper and does not empirically test the model. The scope is Indonesian social commerce and halal cosmetics as a high-credence category. Contribution: MaHACC advances Islamic marketing and digital platform research by (1) operationalizing maqasid congruence as a cognitive appraisal in digital halal consumption, (2) theorizing amanah-based digital trust as a multi-level mechanism linking assurance and co-creation to behavior, and (3) providing testable propositions and an empirical research agenda.